2023
DOI: 10.3390/metabo13030448
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Krüppel-like Factors in Atherogenesis

Abstract: Atherosclerosis is an important problem in modern medicine, the keys to understanding many aspects of which are still not available to clinicians. Atherosclerosis develops as a result of a complex chain of events in which many cells of the vascular wall and peripheral blood flow are involved. Endothelial cells, which line the vascular wall in a monolayer, play an important role in vascular biology. A growing body of evidence strengthens the understanding of the multifaceted functions of endothelial cells, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 177 publications
(258 reference statements)
0
4
0
Order By: Relevance
“…Another important function of KLF4 is its involvement in cross-linking with cellular metabolism [ 53 ]. Glycolysis is known to be the major energy source for endothelial cells, producing up to 85% of ATP [ 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important function of KLF4 is its involvement in cross-linking with cellular metabolism [ 53 ]. Glycolysis is known to be the major energy source for endothelial cells, producing up to 85% of ATP [ 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…As our study centered only on the CACCC-box motif from 150 bp upstream to 300 bp downstream of the TATA-box, hence other relevant KLF binding motifs such as GC-rich regions GC-and GT-were not explored. Therefore, several previously identified genes known to be regulated by KLFs and several processes were not enriched during this study, such as vascular wall homeostasis and atherosclerosis [58,59].…”
Section: Limitationsmentioning
confidence: 91%
“…Although KLFs are found in multiple organ systems, including the cardiovascular, respiratory, gastrointestinal, urinary, neurological, and hematopoietic systems ( 15 ), their tissue expression varies ( Figure 1 ). In other words, some family members are universally expressed, while others are specifically expressed ( 16 18 ). Studies have shown that KLFs possess three highly conserved C2H2 zinc-finger domains in their carboxy-terminal region.…”
Section: Krüppel-like Factorsmentioning
confidence: 99%